Identifying Physical Education Teachers' Perceived Competence and Necessity Regarding Implementation of Alternative Assessment Methods and Their Frequency of Use - Günal, Yurdagül (European Journal of Social Science Education and Research, 2014)
This study aimed at finding out secondary school physical education teachers' overall perception and perceived competence regarding implementing of alternative assessment methods along with frequency of using them. Study participants were comprised of 142 physical education teachers from state schools in Trabzon province during the 2012-2013 education–instruction year. "Teacher Competency" questionnaire developed by Bano?lu (2008) was used. The five-item scale is comprised of four parts. Part one includes demographic data about participants, part two is about "teachers' overall perceptions regarding implementation of alternative assessment methods" (not necessary-quite necessary), part three includes "teachers' perceived competence regarding alternative assessment methods" (unsatisfactory-very satisfactory), and the last part is about "frequency of teachers' using alternative assessment methods (neverquite often)". Data analysis was done at significance level of 0.05 by using "SPSS for WINDOVS 20". in data analysis, frequency, percentage and arithmetic mean were calculated from participants' responses in all of the three parts. Arithmetic mean range was calculated with the logic of 5 columns and 4 ranges. Value of each range was found as 4/5=0,8. Arithmetic mean for teachers' overall perceptions regarding using of alternative assessment methods was found as X= 3.17. According to teachers, alternative assessment methods are moderately necessary as seen from range values obtained from the questionnaire. Portfolio (x=26.1) was found to be the leading alternative assessment method teachers consider not necessary. It was followed by(x=20.4) concept maps. As for the methods considered rarely necessary; performance task (x=17.6) and peer assessment (x=12.7) were found. Under moderately necessary methods, project (x=22.5) and group assessment (x=26.1) were found. Check list (x=49.3) and self assessment (x=43) were listed as necessary methods. Lastly, quite necessary methods were reported as rubric (x=21.1) and check lists (x=14.8). It was understood that mostly teachers regard themselves competent about alternative assessment methods (x=3.53). They find themselves incompetent mainly in relation with concept maps (3.16) and portfolios (x=3.30). The teachers regard themselves competent about check lists, rubric, project, performance tasks, peer assessment, self assessment and group assessment (3.42-4.22). The study revealed that teachers mostly use alternative assessment methods at moderate level (x=3.06). Performance task was found the most frequently used method (x=3.41). It could be inferred from range degrees in questionnaires that according to overall mean of frequency of teachers' using alternative assessment methods (x=3.06), the frequency is low (2,62-3.41). Thus, it could be suggested "frequency of teachers' using alternative assessment methods is mostly not at desired level".
Keywords: Alternative assessment methods, education-instruction